Graphical electrical circuit theory - Boisseau, G (2023)
Most physical systems are naturally compositional and relational, yet our standard mathematical tools rarely reflect that structure. Standard mathematical notation favors terms and functions over relations, making relational reasoning second-class. This changed with the recent development of string diagrams. This 2-dimensional syntax provides the extra flexibility needed for a practical calculus of relations. We build specifically on the development of Graphical Linear Algebra (GLA), a relational calculus for finite-dimensional linear algebra.